2018
DOI: 10.16965/ijpr.2017.264
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Energy Levels of Radial Shock Wave Therapy on Spasticity in Patients With Stroke

Abstract: Background and purpose: Spasticity in the hands and a wrist is a major problem in the management of stroke patients. Different energy levels of shock wave therapy (SWT) have been used for treatment of spasticity. So, the purpose of the study was to compare the effect of two different energy levels of radial SWT on spastic muscles of the hand and wrist in patients affected by stroke. Materials and Methods:Patients randomly assigned into two groups. Group A received the low energy radial SWT while group B receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…The energy levels oscillated between one and four bars. Fouda et al 25 compared two energy levels, for radial extracorporeal shockwave (2 bar, 0.1 mJ/mm 2 , low energy) versus radial extracorporeal shockwave (four bar, 0.18 mJ/ mm 2 , medium energy). The results favoured the medium energy group (see Supplemental Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The energy levels oscillated between one and four bars. Fouda et al 25 compared two energy levels, for radial extracorporeal shockwave (2 bar, 0.1 mJ/mm 2 , low energy) versus radial extracorporeal shockwave (four bar, 0.18 mJ/ mm 2 , medium energy). The results favoured the medium energy group (see Supplemental Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…The PRISMA diagram (see Figure 1) summarizes the results of the scientific literature search. Sixteen randomized controlled trials were included: these were by Bae et al, 15 Santamato et al, 16 Fouda et al, 17 Dymarek et al, 18 Kim et al, 19 Li et al, 20 Yoon et al, 21 Duan et al, 22 Guoxing et al, 23 Guo et al, 24 Fouda et al, 25 Kamaluddin et al, 26 Park et al, 27 Wu et al, 28 Ahmed et al, 29 and Li et al 30 Studied identified but not included are shown in Appendix 2. No author responded when contacted for additional information.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation